Marriage, dispensation and divorce during the years of Henry VIII's 'great matter': a local case study. Issue 1 (2nd January 2019) - Owen, Gwilym; Probert, Rebecca
ABSTRACT: The facts surrounding Henry VIII's divorce from Catherine of Aragon are well known. What is less well known is the effect which these events had on the lives of the Crown's subjects. Little has been written on the topic given the fact that annulments of marriage within the prohibited degrees were rare. The authors have unearthed evidence concerning the various marriages of Edward Griffith of the Penrhyn estate in north-west Wales which took place during the time of Henry VIII's repudiation of Catherine of Aragon in favour of Anne Boleyn. At one level, the narrative suggests that Edward Griffith followed closely what was happening at court when making his matrimonial choices. On another level, it is suggested that Edward's actions may be explained by reference to native Welsh marriage law. The article also considers, by reference to primary sources, the matrimonial litigation which resulted from Edward's various marriages. These are derived from sources which are external to the church courts. The article poses the question as to whether Edward's marriages and actions were exceptional in terms of events, or whether there could have been further challenges concerning inheritance and dower, the evidence for which has simply not survived. The article highlights the importance of considering legal actions in a wider social, cultural and political context. In the case of Edward Griffith, although he came from an aristocratic family, there is evidence that some of his settlement patterns tended to mimic customary Welsh law. It is suggested, therefore, that some of his actions in respect of his marriages may also be explained by reference to Welsh identity.